2019
DOI: 10.1002/celc.201900116
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid Quaternary Ammonium Surfactants Based on Renewable Resources as a Leveler for Copper Electroplating

Abstract: A series of fatty acid quaternary ammonium surfactants (FAQAS 1 a–1 f) derived from renewable resource of fatty acid have been rationally designed and investigated as levelers applied in copper electroplating. Surface tension and contact angle indicated the FAQAS's surfactivity and wettability were closely related to the length of hydrophobic chains. FAQAS 1 a–1 f displayed the capability to inhibit the copper deposition in CV tests and their inhibiting abilities agreed with the order of their surfactivity and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…In contrast, it is likely that HBP was weakly adsorbed on the liquid–solid interface by the hydrophobic alkyl group rather than the adsorption of the pyridinium cation through electrostatic attraction. 28 Therefore, it was found that binary HBP + PTB exhibited the highest mass gain through the process of simultaneous adsorption, which could be explained by relatively uniform surface covering of HBP and the strong adsorption of PTB.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…In contrast, it is likely that HBP was weakly adsorbed on the liquid–solid interface by the hydrophobic alkyl group rather than the adsorption of the pyridinium cation through electrostatic attraction. 28 Therefore, it was found that binary HBP + PTB exhibited the highest mass gain through the process of simultaneous adsorption, which could be explained by relatively uniform surface covering of HBP and the strong adsorption of PTB.…”
Section: Resultsmentioning
confidence: 98%
“…The higher change in mass in the presence of PTB could primarily be related to electrostatically sensitive adsorption, in view of the fact that the positively charged nitrogen of the quaternary pyridine ring was strongly adsorbed by the applied current. In contrast, it is likely that HBP was weakly adsorbed on the liquid–solid interface by the hydrophobic alkyl group rather than the adsorption of the pyridinium cation through electrostatic attraction . Therefore, it was found that binary HBP + PTB exhibited the highest mass gain through the process of simultaneous adsorption, which could be explained by relatively uniform surface covering of HBP and the strong adsorption of PTB.…”
Section: Resultsmentioning
confidence: 99%
“…The throwing power ( TP ), a crucial indicator to characterize the thickness uniformity of the copper coating in the THs, was obtained according to the cross‐section images [46–48] . The throwing power ( TP ) value was calculated by the Equation (5).…”
Section: Methodsmentioning
confidence: 99%
“…The throwing power (TP), a crucial indicator to characterize the thickness uniformity of the copper coating in the THs, was obtained according to the cross-section images. [46][47][48] The throwing power (TP) value was calculated by the Equation ( 5). The H a , H b , H c , H d , H e and H f in the formula were the electroplated copper coating thickness presented in the Figure 8.…”
Section: Electroplating Experimentsmentioning
confidence: 99%
“…Copper is chosen as the filling metal on account of its high electromigration resistance and an excellent thermal (401 W·m –1 K –1 ) and electrical conductivity (1.67 μΩ·cm). Acidic sulfate copper electronic electroplating is the most popular process to realize void-free filling. …”
Section: Introductionmentioning
confidence: 99%